(untitled) (IIUC Studies, 2016)
Caribbean poet Derek Walcott , in his commitment to the Caribbean and, of course, with artistic excellence, disappointingly finds his nation still confined to marginalization which is self-imposed, though it was colonially imposed during the colonial period. The issues contributing to this self-imposed marginalization, an otherwise colonial legacy, are the exigent factors Walcotts relentless poetic efforts address. This paper aims at exploring how Walcott s unalloyed poetic dedication of epistemological siginificance, with a view to strengthening the Antillean from within, concentrates on the marginalized nations unconscious, imprudent and self-centred thoughts and measures in the issues of Caribbean self, tourism, urbanization, governance, literary tradition and uniqueness of literature in a post-colonial context of agressive Euro-American economy and culture. IIUC Studies Vol.12 December 2015: 87-100